Pengaruh Media Pop Up Book Terhadap Hasil Belajar Siswa Materi Pancasila Kelas 1 SDN 3 Keyongan - Sholekah, Amalia; Permata, Santy Dinar; Rahmawati, Arum Dwi (Civiliza Publishing, Indonesia., 2023)
This research aims to see whether the learning outcomes of class I students at SDN 3 Keyongan on Pancasila material are influenced by the use of pop up book learning media compared with student learning outcomes if they do not use pop up book learning media. The population in this study were all students at SDN 3 Keyongan with class I subjects at SDN 3 Keyongan totaling 20 students. This research uses a quantitative type of research with a pretest posttest control group research design. The data collection technique uses saturated samples. Data collection techniques use pretest and posttest, each consisting of 25 multiple choice questions. Test the prerequisites through a normality test using the Kolmogorov Smirnov test. The normality test results for the pretest questions were 0.200 > 0.005 and the posttest questions were 0.200 > 0.05 so the data was in normal condition. The results of data analysis used the Paired Sample T-Test assisted by SPSS Version 16 Windows with 0.000 < 0.05. So, Ha is accepted, namely that there is a difference in learning outcomes for Pancasila material between those who use pop up book learning media and those who do not use pop up book learning media.